The Impacts of Canadian Social Program Reform on Job Tenure of Newer Jobs from 1976-2010 - Wu, Qingrui (Université d'Ottawa | University of Ottawa, 2011)
In this paper I use the 1976-2010 Canadian Labour Force Survey to examine the impact of specific program reforms on the aggregate employment rate and the one-year retention rate for workers with less than one year of job tenure. In particular, I focus on